Privacy Laws and Biobanking in Germany. Issue 1 (March 2016) - Hoppe, Nils
While the possibility of enacting a sui generis Biobank Act has been debated in Germany at great length, as of yet the country has not implemented any biobankspecific legislation. Instead, oversight is available via a network of research and privacy laws, including those of the European Union. The Nationale Kohorte, Germany's large-scale, population-based epidemiological research biobank, is funded by the Federal Ministry of Education and Research, and there are currently 108 registered bio-banks throughout Germany. The current system, including the structure and study design of the Nationale Kohorte, privileges the protection of personal information even at the cost of socially desirable research; it remains to be seen if forthcoming legislation will shift this balance.